Influence of patient characteristics on chimeric antigen receptor T cell therapy in B-cell acute lymphoblastic leukemia - Furun An (Nature Portfolio, 2020)
CAR T therapy has some efficacy in the treatment of patients with refractory/relapsed B-cell acute lymphoblastic leukemia; however in some patients further relapse is encountered. Here, the authors conduct a Phase II clinical trial of a CD19 CAR T and demonstrate that patients with extramedullary disease are more likely to relapse than those without.